JAMINAN DAN PERLINDUNGAN PERLINDUNGAN UPAH PEKERJA/BURUH DALAM KEPAILITAN MENURUT UNDANGUNDANG NOMOR 37 TAHUN 2004 TENTANG KEPAILITAN DAN PENUNDAAN KEWAJIBAN PEMBAYARAN UTANG - , Sherly Fitriyana ([Yogyakarta] : Universitas Gadjah Mada, 2014)
The goals to be achieved by the author through this thesis research, is to determine the Law Number 37 of 2004 concerned on Bankruptcy and Suspension of Payment in accomodating dan ensuring the wages of workers/laborers in bankruptcy and to determine the relationship and the responbililities of the curator to the rights of workers/laborers who are not accomodated. This research conducted by the normative juridical method. The data which used in this study consisted of primary data, secondary data, and tertiary data. Primary data obtained from the national law and jurisprudence, secondary data obtained from examining the books and conference papers related to the employment law and bankruptcy law, and the tertiary data obtained by internet data. The results of the study were analyzed qualitatively and deductively. From the results of this study concluded that the weak position of workers / laborers to obtain rights (wages) in the case of bankruptcy due to the absence of a clear and unequivocal interpretation giving rise to the denial of the rights of the workers / laborers in the company they work who are experiencing bankruptcy by the commercial court decision. To that end, the Government / State must close the legal loopholes to make improvements Law that is mutually supportive and complementary so there is no conflict or disharmony between bankruptcy law and PKPU and labour Law, Government / State also needs to regulate the relationship between the workers / laborers and through various regulations Curator concrete, so there is a legal guarantee of the rights of workers / laborers at the time the debtor is declared bankrupt and all the maintenance switch to the curator as a substitute for entrepreneurs. Keyword: Laborers, Wages, Bankruptcy, Curator